Graphene oxide-embedded nanocomposite membrane for solvent resistant nanofiltration with enhanced rejection ability - Ding, R.; Zhang, H.; Li, Y.; Wang, J.; Shi, B.; Mao, H.; Dang, J.; Liu, Jian (Pergamon, 2015)
© 2015 Elsevier Ltd. Herein, novel solvent resistant nanofiltration membranes with enhanced rejection ability are synthesized by embedding graphene oxide (GO) sheets into polyethyleneimine (PEI) matrix, using polyacrylonitrile (PAN) ultrafiltration membrane as support layer. Dopamine is employed to modify the surface of PAN for enhancing the adhesive strength between the active and support layer and meanwhile promoting the dispersion of GO within PEI. Fourier transform infrared spectroscopy, scanning electron microscope, thermogravimetric analysis, and contact angle measurement are conducted to probe the microstructures of the membranes. The nanofiltration performances in terms of solvent uptake, area swelling, solvent flux, and solute rejection of the membranes are systematically investigated using four commonly-used solvents, including ethanol, acetone, ethyl acetate, and n-heptane. It is found that GO sheets are horizontally-aligned within PEI matrix and generate unique transfer pathways through the GO edges, allowing small-sized molecules to transport while rejecting big-sized solute molecules. Consequently, the membranes display enhanced solute rejection and adequate solvent flux. 3.0wt% GO sheets increase the rejection of polyethylene glycol (Mw 200) from 66.2% to 96.8% with the acetone flux of 15.7 Lm-2h-1, particularly. In addition, the incorporation of GO donates promising long-term operation stability and excellent solvent resistance for practical application.